Prediction of Sleep Quality in Cancer Survivors Based on Arousal, Pain, and Worry: The Mediating Role of Dysfunctional Beliefs and Attitudes About Sleep - Omid Amani; Mohammad Ali Mazaheri; Mona Malekzadeh Moghani; Fariba Zarani (Cancer Medicine)
ABSTRACT Purpose Our study explores the prevalence, severity, and psychological correlates of insomnia in cancer survivors, aiming to predict sleep quality based on pre‐sleep arousal, pain, and worry, while examining the mediating role of dysfunctional beliefs and attitudes about sleep (DBAS). Methods A descriptive‐correlational design was employed, with 200 cancer survivors from Tehran, Iran, selected through convenience sampling in 2022. Participants completed the Pittsburgh Sleep Quality Index (PSQI), Chronic Pain Grade (CPG), Dysfunctional Beliefs and Attitudes about Sleep Scale (DBAS), Pennsylvania Worry Questionnaire (PSWQ), and Pre‐Sleep Arousal Scale (PSAS). The data were analyzed using correlation and multiple regression through SPSS‐23 software. Results On average, 37.07 months post‐treatment, 95% of survivors reported delayed sleep onset, 88.5% frequent awakenings, 72% reduced sleep duration, and 67% morning dysfunction. Significant positive associations were found between pre‐sleep arousal, chronic pain (r = 0.552), worry (r = 0.161), DBAS (r = 0.363), and poor sleep quality (r = 0.607). Regression analysis indicated that physical arousal (B = 0.29, p = 0.01) and DBAS (B = 0.14, p < 0.05) were significant predictors of sleep quality, with DBAS mediating the relationship between physical arousal and sleep quality. Conclusions Persistent sleep problems after cancer treatment highlight the need for targeted interventions in survivorship care. Sleep‐focused strategies may improve sleep quality and reduce the burden of insomnia‐related issues. Implications for Cancer Survivors Addressing pre‐sleep arousal, pain, worry, and DBAS through targeted interventions is crucial for improving sleep quality and overall quality of life in cancer survivors.